Boris Karloff Icons of horror collection (Culver City, Calif. : Sony Pictures Home Entertainment, 2006)
"The black room": Twin brothers - one good, one evil - live in a small country where beautiful women seem to turn up missing. "The man they could not hang" and "Before I hang" A forward-thinking scientist runs afoul of the law and becomes a crazed killer. "The boogie man will get you" : Nathaniel sells his house off to a naive young woman but stays in order to continue work on his experiments of making superman out of door-to-door salesmen.
Disc 1: The black room ; The man they could not hang -- Disc 2: Before I hang ; The boogie man will get you.
"The boogie man will get you" is based on a story by Hal Fimberg and Robert B. Hunt.
"The black room" originally released as a motion picture in 1935 ; "The man they could not hang" originally released as a motion picture in 1939 ; "Before I hang" originally released as a motion picture in 1943 ; "The boogie man will get you" originally released as a motion picture in 1942.
"The black room" cast: Boris Karloff, Marian Marsh, Robert Allen.
"The man they could not hang" cast: Boris Karloff.
"Before I hang" cast: Boris Karloff, Evelyn Keyes, Bruce Bennett.
"The boogie man will get you" cast: Boris Karloff, Peter Lorre, Maxie Rosenbloom, Larry Parks, Jeff Donnell.
Keywords: Twins -- Drama; Hanging -- Drama; Scientists -- Drama; Science -- Experiments -- Drama; Thrillers (Motion pictures, television, etc.); Feature films; Comedy films; Video recordings for the hearing impaired